Does Managerial Owneship and Islamic Corporate Social Responsibility Reduce Tax Aggressiveness? - Indriastuti, Maya; Mar'ati, Fudji Sri; Wijayani, Dianing Ratna (IJIBE (International Journal of Islamic Business Ethics), 2020)
This study aims to test empirically the effect of managerial ownership on tax aggressiveness with Islamic corporate social responsibility as the intervening variable. The populations of this study were all entities listed in Jakarta Islamic Index from 2015-2019. 40 entities were obtained by using purposive sampling technique. All data were analyzed by using multiple linear regression analysis and sobel test. The results showed that managerial ownership has a significant positive effect on Islamic corporate social responsibility. In contrast, managerial ownership has a negative and insignificant effect on tax aggressiveness. Furthermore, Islamic corporate social responsibility has a significant negative effect on tax aggressiveness and Islamic Corporate Social Responsibility is able to moderate the effect of managerial ownership on tax aggressiveness.